# heroatrangi

Lv10

## Guru Gobind Singh Indraprastha University - GGSIPU

16 Followers
0 Following
95 Helped

Published1458

### Subjects

Architecture1History3Law1Management2English194Philosophy1Anthropology3Astronomy11Business7Science30Electrical Engineering8Mechanical Engineering6Prealgebra1Sociology4Geography3Ethics1Information Technology3Algebra274Precalculus16Engineering4Computer Science2Accounting1Calculus60Biology45Mathematics364Statistics10Physics170Economics22Chemistry211
When heat transfer is at constant volume then no work is done but when heat tr...
Answer: Assumption - The resources available for their survival remain constan...
Initial velocity = d(y)/dx at x=0 dy/dx= 0.4741 m/s Acceleration = d/dx (dy/dx...
Answer: Magnetic flux density is representation of direction & strentgh of...
Option 1 i.e. to advance or to continue is best option.
Answer: Suppose that a group discussion is going on and one person name A is u...
Answer: dQ = dE + pdV dQ = +824 J pdV = +650 J dE = 824-650 = 174 J Since it i...
Answer:Assuming the pressure remain constant. V1/T1 = V2/T2 50/(273+25)= V2/(2...
Answer: e^lnx Let e^lnx = y ln(e^lnx) = lny lnX = lnY X= Y Thus e^lnX = X
Answer: Sin⁴x - Cos⁴X (Sin²X+ Cos²X)(Sin²X- Cos²X) -(Cos²X- Sin²X) -Cos2X
Answer:√225 =√(15×15) = 15
Answer: √68 =√(2×2×17) =2√17
Answer: Sin⁴x- Cos⁴X =(Sin²X+Cos⁴X)(Sin²X- Cos²X) =-(Cos²X-Sin²X) =-Cos2X
Answer: X³-9x =X(X²-9) =X(X+3)(X-3)
Answer:X²-x-6 = X²-6x+x-6 = X(X-6)+1(X-6) = (X-6)(X+1)
Answer: 2x²+7x+3= 2x²+6x+X+3=2x(X+3)+1(X+3) =(X+3)(2X+1)
Answer: X²- Y² (X-Y)(X+Y)
Answer: X³+27 X³+3³ (X+3)(X²-3X+9)
Answer: Fractional notation for 37.5% = 37.5/100 =375/100
Answer: n=nE(n^(n-1))n=1 Where E represents summation.
Answer: = -√3sinx +cosxDividing & multiplying by 2 =2((-√3sinx)/2 +(1/2) c...
Answer: TanQ = √(1-cos²Q)/cosQ
Answer: TanQ = √(1-cos²Q)/cosQ
Answer: TanQ = √(1-cos²Q)/cosQ
Answer: Secx = 1/√(1-sin²x)
Answer: Log(12) Log(2² ×3) Log(2²) +log(3) 2log2 +log(3)
Answer: Sec(π/4) =1/cosine(π/4) =√2
Answer: Sec(π/4) = 1/cosine(π/4) =1/(1/√2)) =√2
Answer: f(a+h) = (a+h)²-2(a+h)+3 f(a) = a²-2a+3 f(a+h)-f(a) = a²+h²+2ah-2a-2h ...
Answer: Cos(11π/12) =Cos(π-π/12) =-Cos(π/12) =-Cos(π/12)=-0.9659
Answer: Let log(27)9 = x9 = 27^x 3² = 3^(3x) 2= 3x X= 2/3
Answer: Sin X= 1/2 X= 30°
Answer: Cos(11π/12) =Cos(π-π/12) =-cos(π/12)
Answer: Sin X= (1/2) X= 30°
Answer: Sin X= (1/2) X= 30°